Changes in the national structure of Serbia’s population at the beginning of the 21st century - Stojšin, Snežana (Sociološki pregled, 2023)
The main aim of this paper is to analyze the national structure of Serbia’s population according to the 2022 Census and the changes occurring since the beginning of the 21st century.(Census, 2002) to date (Census, 2022). The research starts from the assumption that there have not been substantial changes in the national structure of Serbia’s population in comparison to two previous censuses (2002 and 2011), but that certain changes can be seen at the municipal level. During the observed period, the number of Serbia’s inhabitants dropped by 850,998. The data analysis shows that the reduction in the number of inhabitants was seen in almost all ethnic groups during the observed period. There was an increase in the number of members of Bosniak, Roma, Albanian and Russian nationalities. All ethnic groups are older in comparison to the previous censuses.
Keywords: national structure of population; Serbia; census methodology; 2022 Census